Bridging the Knowledge Gap through Organic Field School (OFiS) Method for Long Pepper (Piper longum) Farmers in Wonogiri, Indonesia - Suswadi Suswadi; Mutiarra Ridyo Arum; Arbianti Arbianti; Tyas Soemarah Kurnia Dewi; Supartini Supartini; Moh Erkamim (PRIMA: Journal of Community Empowering and Services, 2025)
Organic certification is urgently needed for long pepper to meet global market standards and enhance product credibility. Wonogiri Regency is the largest center for long pepper production in Central Java, with this biopharmaceutical commodity cultivated for generations. Its promising market potential necessitates meeting global standards, including organic certification. This community service initiative aims to bridge knowledge gaps and improve farming practices through Good Agricultural Practices (GAP) for organic long pepper. The methods used include classroom activities to assess farmer knowledge and transfer knowledge through socialization and field activities in demonstration plots, starting with the identification of farmer training priorities. A pre-test survey revealed that while over 65% of farmers understood the planting stage, less than 50% were familiar with land preparation, planting, and harvesting. This low level of knowledge is due to a lack of information on farming practices that comply with organic Good Agricultural Practices (GAP). Key training priorities identified include: (1) preparation and application of organic fertilizers and pesticides, (2) propagation of organic long pepper seeds, and (3) post-harvest handling. To address these, the Organic Field School (OFiS) was established as a training platform, equipping farmers with practical skills. The results indicate that farmers gained significant knowledge and can now independently implement organic long pepper cultivation. OFiS method can bridge the farmer’s knowledge gap, increase farmers’ knowledge in preparation, growing, planting, and harvesting based on Good Agricultural Practices (GAP). OFiS serves as an effective solution to enhance sustainable agricultural practices, supporting farmers in producing high-quality organic long pepper that meets global standards.